Barley genotypic β-glucan variation combined with enzymatic modifications direct its potential as a natural ingredient in a high fiber extract. (May 2017) - Mikkelsen, Mette S.; Meier, Sebastian; Jensen, Morten G.; Qin, Fen; Stoica, Iuliana-Madalina; Martens, Helle J.; Blennow, Andreas; Jespersen, Birthe M.
Abstract: β-Glucan dietary fiber rich food systems hold a great potential for improving human health. Here, we evaluate the extractability and quality of β-glucan liquid formulations from eight different barley genotypes varying in β-glucan content and molecular structure using Termamyl ® SC (T), Attenuzyme ® (A) and Attenuzyme ® Flex (AF) amylolytic enzymes in combinations. Extracts from barley lines Lys5f, KVL408, KVL1104 and CDC Fibar exceeded 4 g β-glucan/l, providing European Food Safety Authority (EFSA) and U.S. Food and Drug Administration (FDA) recommended amounts (3 g β-glucan/day) from three portions. TAF extracts of Lys5f and KVL408 grains reached extraordinary high concentrations of 8–9 g β-glucan/l. The β-glucan molecular mass decreased with enzyme treatment T < TA < TAF due to minor lichenase side activity. Extractability was generally higher and molecular mass lower for barley lines low in triosyl/tetraosyl (DP3/DP4) ratios than for those high in DP3/DP4 ratios (Lys5f, KVL408 and KVL1104). Overall, the higher β-glucan content and structural robustness in Lys5f and KVL408 raw materials favor these in a β-glucan rich extract with potential for EFSA and FDA health and nutrition claims. Highlights: Screening of barley genotypes for high β-glucan (BG) extraction yields. High BG grain content correlate with high BG triosyl/tetraosyl (DP3/DP4) molar ratio. Lichenase side activity from amylolytic enzymes cause controlled BG degradation. Lys5f and KVL408 barley extracts meet EFSA and FDA BG health claim criteria.